Pelayanan Prima Keperawatan di Pelayanan Primer: Perspektif Perawat dan Pasien - Deby Zulkarnain Rahadian Syah; Junaiti Sahar; Krisna Yetti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the perception of excellent service at Pandak II Public Health Center Bantul Yogyakarta. The method used is qualitative research by conducting in-depth interviews with providers and users of nursing services at the Puskesmas. The validity of the data is done by the triangulation method. The results showed that the themes obtained were: 1) giving a sense of pleasure; 2) friendly and attentive; 3) satisfying as expected; 4) promotive, preventive, curative and rehabilitative services; 5) nursing education facilities; 6) limitations of two-way communication; 7) individual leadership and management style; 8) professional; 9) success of government programs; 10) regulation of the application of nursing care in primary care; 11) HR management; 12) time management; 13) friendliness, attention, speed, thoroughness. In conclusion, there are 13 themes perceived by participants related to excellent service in primary care. Keywords: Patient, Primary Health Service, Excellent Service, Nurse, Public Health Center